The concise Corsini encyclopedia of psychology and behavioral science - Craighead, W. Edward; Nemeroff, Charles B. (John Wiley & Sons, 2004)
Contains entries in all major categories of psychology - written by esteemed authorities in their fields. Provides comprehensive coverage from Acquired Drives to Z-score, from conduct disorders to shamanism.-- xreferplus description.